Genetic overlap between major depressive disorder and obstructive sleep apnea - Lin, Fangbo; Deng, Yanyao; Xiao, Le; Liu, Chao; Li, Jie (Frontiers in Psychiatry, 2024)
In this work, we conducted a large genome-wide association summary statistics(GWAS) to investigate the pleiotropic associations between MDD and obstructive sleep apnea in single nucleotide polymorphism (SNP) levels, gene levels and explore the biological pathways. We also employed a two-sample Mendelian randomization analysis (MR) to examine the causal relationship between the two traits. This was the first article to systematically examine the link between MDD and neurodegenerative disease from a genetic perspective, and it demonstrated the relevance of neurodegenerative disease to the occurrence and development of mental disorders from a biological standpoint.